The Effects of an Inference-Making Strategy Taught With and Without Goal Setting. (August 2016) - Reed, Deborah K.; Lynn, Devon
This quasi-experimental study examined the effects of a strategy for making text-dependent inferences—with and without embedded self-regulation skills—on the reading comprehension of 24 middle-grade students with disabilities. Classes were randomly assigned to receive the inference intervention only (IO), inference + individual goal setting (IIG), or inference + group goal setting (IGG). The Kruskal–Wallis one-way analysis of variance revealed no significant differences between groups on overall reading comprehension performance, but students in the IGG group significantly outperformed the IO and IIG groups on evaluation items, χ 2 (2, N = 24) = 13.18, p = .001. Paired samples t tests indicated all groups significantly improved their comprehension performance from pre- to posttest, IO: t (8) = 2.76, p < .05; IIG: t (6) = 3.97, p < .01; IGG: t (7) = 4.35, p < .01. The IGG group wrote significantly more valid inferences in Lessons 3 to 7 than the IO or IIG groups; χ 2 (2) ranged from 7.26, p < .05, to 16.16, p < .001.